Toxicity and Local Tolerance of COVID- eVax, a Plasmid DNA Vaccine for SARS-CoV-2, Delivered by Electroporation. (October 2021) - Ramot, Yuval; Caselli, Gianfranco; Aurisicchio, Luigi; Andreini, Isabella; Marra, Emanuele; Luberto, Laura; Stoppoloni, Daniela; Pacello, Maria Lucrezia; Monetini, Laura; Nyska, Abraham
COVID-19 is a rapidly spreading disease, posing a huge hazard to global health. The plasmid vaccine pTK1A-TPA-SpikeA (named COVID- e Vax) encodes the severe acute respiratory syndrome coronavirus 2 S protein receptor-binding domain, developed for intramuscular injection followed by electroporation (EP). The aim of this study was to assess the systemic toxicity and local tolerance of COVID- e Vax delivered intramuscularly followed by EP in Sprague Dawley (SD) rats. The animals were killed 2 days and 4 weeks after the last injection (30-day and 57-day, respectively). No mortality was observed, and no signs of toxicity were evident, including injection site reactions. A lasting and specific immune response was observed in all treated animals, confirming the relevance of the rat as a toxicological model for this vaccine. Histopathological evaluation revealed muscle fiber necrosis associated with subchronic inflammation at the injection sites (at the 30-day time point), with a clear trend for recovery at the 57-day time point, which is expected following EP, and considered a desirable effect to mount the immune response against the target antigen. In conclusion, the intramuscular EP-assisted DNA vaccine, COVID- e Vax showed an excellent safety profile in SD rats under these experimental conditions and supports its further development for use in humans.